The fuel multiplier in multi-stage supply chains. (January 2015) - Regnier, Eva; Simon, Jay; Nussbaum, Daniel A; Whitney, Laura K
Fuel requirements on the battlefield impose direct costs associated with the resources necessary to transport the fuel and protect logistics assets, in addition to indirect energy security costs. Estimating the enterprise-wide demand for fuel associated with fuel consumption on the battlefield is a challenging, but necessary, step to making good decisions. This paper presents a modeling framework for estimating the enterprise-wide fuel requirements associated with a multistage fuel supply chain, demonstrating a multiplicative increase in fuel demand with additional stages, and examining the fuel impact of protecting the supply chain.